Public spending and natural resources development: a way toward green economic growth in China - Guo, Yating; Rosland, Anitha; Ishak, Suryati; Muhammad Senan, Mohammad Khair Afham (Elsevier, 2023)
The economic rise of China over the past few decades has been nothing short of remarkable. This growth, however, has brought about significant challenges, particularly in terms of environmental sustainability and natural resource management. Through a comprehensive GARCH data analysis spanning 2008 to 2018, the research explores the intricate relationship between public spending patterns and the advancement of green technologies and industries. By focusing on the prudent allocation of resources, particularly in the realm of natural resource utilization, the study assesses China’s progress toward fostering a greener economic landscape. This investigation offers insights into the intricate dynamics that underpin the nation’s ongoing commitment to balancing economic expansion with ecological preservation. The findings shed light on the policy effectiveness and long-term implications of China’s sustainable development initiatives, providing valuable considerations for both policymakers and researchers invested in the sustainable growth paradigms of emerging economies.